A Literature Review on Tax Compliance in Indonesia In Increasing State Revenue - Ady Setyo Nugroho; Handayani, Nur (Jurnal Ilmu Pemerintahan Widya Praja, 2025)
Tax has long been one of the components of state revenue that cannot be separated from the life of society. Therefore, a supportive tax policy is needed. This policy should still consider all aspects that influence the lack of tax compliance. This research method is a literature review with a qualitative approach. The results obtained show that the factors impacting tax compliance are: 1) tax awareness; 2) perception of justice; 3) tax sanction enforcement; 4) economic factors; and 5) education factors.